Hubungan Kompetensi Sosial Dengan Komunikasi Interpersonal Pada Siswa - Reno Diqqi Alghzali (Jurnal Dakwah dan Komunikasi, 2022)
The problem that occurs at the school level is that students often look less able to communicate with their teachers when they pass by or just to reprimand the teacher, unless the teacher has taught them in their class, often students do not listen and obey the advice of the teacher. From the problems above Researchers have a goal to explain social competence in students, explain interpersonal communication to students and examine the relationship between social competence and interpersonal communication. This study uses quantitative methods with correlational quantitative descriptive data analysis techniques that are processed with the SPSS program. The results of the research conducted indicate that social competence and interpersonal communication are low, the results of the correlation test in research on the relationship between social competence and interpersonal communication obtained a Pearson correlation value or score on r count of 0.833, when compared to r table of 0.000. Social competence with interpersonal communication of rxy = 0.833 with a significant level of p = 0.272. This means that the significance is greater than 0.05 (0.000>0.05), then Ho is rejected. This means that there is a significant relationship between social competence and interpersonal communication in students.